The expression of renin-angiotensin system components in human carotid plaque - Kolaković, Ana; Bundalo, Maja; Djurić, Tamara; Končar, Igor; Stanković, Alksandra; Živković, Maja (Vojnosanitetski pregled, 2024)
Background/Aim. The renin-angiotensin system (RAS) is linked to the development of atherosclerosis (As), including its initiation and progression. Besides the well-known angiotensin-converting enzyme (ACE), two newer RAS family members are related to vascular remodeling – ACE2 as a homolog of ACE and collectrin [transmembrane protein 27 (TMEM27)] as a homolog of ACE2. Up to now, a limited number of studies have examined the expression of these RAS components in advanced carotid plaque (CP) tissue based on the sex of the patients and plaque phenotypes (PPs). There are two ultrasonographically defined PPs – the hypoechogenic plaque (HoP) and the hyperechogenic plaque (HerP) phenotype. The aim of the study was to investigate whether there was a correlation between the expression of RAS components in the CP and the sex and PPs of patients. Methods. We examined 74 patients with advanced CP who underwent carotid endarterectomy. The intraplaque expression of RAS components was determined with the real-time polymerase chain reaction, using the TaqMan® gene expression assays and Western blot. A two-way ANOVA followed by a post-hoc Tukey test was performed for the statistical analysis of results. Results. No interaction was recorded between the sex of the patients and PPs in influencing the relative expression of ACE and TMEM27 messenger RNA (mRNA) (p > 0.05). In 56.06% of plaque samples, no expression of ACE2 mRNA was detected. Among the plaques where ACE2 mRNA expression was detected, its expression level was higher in females with the HoP phenotype compared to females with the HerP phenotype (p < 0.001). In patients with the HoP phenotype, females had higher expression of ACE2 mRNA than males (p < 0.05). In the male study group, ACE protein levels were significantly lower in the HoP phenotype compared to the HerP phenotype (p < 0.001). Females with the HoP phenotype had significantly higher ACE protein levels than males with the HoP phenotype (p < 0.0001). Conclusion. Our results revealed alterations in the expression levels of ACE and ACE2, at the mRNA and protein levels, in advanced carotid As. These alterations are impacted by sex and PP and may indicate a switch from the balanced RAS/ACE/ACE2 axis in the healthy blood vessel to the unbalanced axis in vascular remodeling due to As.